2019
DOI: 10.1016/j.immuni.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type-Specific Responses to Interleukin-1 Control Microbial Invasion and Tumor-Elicited Inflammation in Colorectal Cancer

Abstract: Chronic inflammation drives the progression of colorectal cancer (CRC). Increased expression of interleukin (IL)-17A is associated with poor prognosis, and IL-17A blockade curbs tumor progression in preclinical models of CRC. Here we examined the impact of IL-1 signaling, a key regulator of the IL-17 pathway, in different cell types within the CRC microenvironment. Genetic deletion of the IL-1 receptor (IL-1R1) in epithelial cells alleviated tumorigenesis in the APC model of CRC, demonstrating a cellautonomous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 50 publications
2
101
0
1
Order By: Relevance
“…The role of IL-1 in colorectal cancer was recently dissected by using cell-type-specific IL-1R1-deficient mice. This study showed that IL-1 had pro-tumor effects by promoting Th17-mediated inflammation through IL-17 and IL-22, and epithelial-cell-autonomous mechanisms, whereas IL-1 had tumor-suppressive effects by promoting neutrophilmediated control of bacterial invasion (Dmitrieva-Posocco et al, 2019).…”
Section: Il-1 Family Members In Maintenance Of Homeostasis and Gastromentioning
confidence: 78%
“…The role of IL-1 in colorectal cancer was recently dissected by using cell-type-specific IL-1R1-deficient mice. This study showed that IL-1 had pro-tumor effects by promoting Th17-mediated inflammation through IL-17 and IL-22, and epithelial-cell-autonomous mechanisms, whereas IL-1 had tumor-suppressive effects by promoting neutrophilmediated control of bacterial invasion (Dmitrieva-Posocco et al, 2019).…”
Section: Il-1 Family Members In Maintenance Of Homeostasis and Gastromentioning
confidence: 78%
“…Indeed, a recent study has elegantly demonstrated opposing roles of cell-type specific IL-1R signaling in CRC. The protumorigenic roles of IL-1R in epithelial and T-cells are counteracted by its effects on myeloid cells, particularly neutrophils, where IL-1R signaling contributes to deter tumorinfiltrating bacteria and dampen CRC promoting inflammation 99 . A similar approach has been studied for the role of ASC in skin tumorigenesis, where inflammasome activation driven by ASC in myeloid cells favors epithelial skin tumorigenesis, whereas ASC in keratinocytes serves to limit proliferation, possibly through p53 activation in an inflammasome-independent manner 100 .…”
Section: Protection In Colorectal Cancermentioning
confidence: 99%
“…On the flip side, IL-22 has been shown to promote tumor growth in some models (Dmitrieva-Posocco et al, 2019; Kirchberger et al, 2013). This is consistent with the fact that IL-22 is a potent activator of STAT3 in epithelial cells, and STAT3 is required for the development of colitis-associated cancer (Bollrath et al, 2009; Grivennikov et al, 2009).…”
Section: Cancermentioning
confidence: 99%